Monitoring Social and Economic Impacts of COVID-19 on Refugees in Uganda : Results from the High-Frequency Phone - Third Round - World Bank (World Bank, Washington, DC, 2021)
The High-Frequency Phone Survey for refugees in Uganda (URHFPS) tracked the socioeconomic impacts of the COVID-19 (coronavirus) crisis on refugees throughout three rounds. The World Bank (WB) in collaboration with the Uganda Bureau of Statistics (UBOS) and the United Nations High Commissioner for Refugees (UNHCR) launched and conducted the URHFPS. The URHFPS tracked the impacts of the pandemic between October 2020 and March 2021. Data collection for the first round of the URHFPS took place between October 22 – November 25, 2020, the second round took place between December 5-24, 2020, and the final and third round was conducted between February 8-March 14, 2021. This brief discusses the results from the third round. Where possible and appropriate, the results are compared across the three rounds and also benchmarked against Ugandans by using the national High-Frequency Phone Survey on COVID-19 (UHFPS). Detailed results for the first round are available in Atamanov et al. (2021a) and for the second round in Atamanov et al. (2021b)